2013
DOI: 10.1038/srep02889
|View full text |Cite
|
Sign up to set email alerts
|

CAR regulates epithelial cell junction stability through control of E-cadherin trafficking

Abstract: CAR (Coxsackie and Adenovirus Receptor) is the primary docking receptor for typeB coxsackie viruses and subgroup C adenoviruses. CAR is a member of the JAM family of adhesion receptors and is located to both tight and adherens junctions between epithelial cells where it can assemble adhesive contacts through homodimerisation in trans. However, the role of CAR in controlling epithelial junction dynamics remains poorly understood. Here we demonstrate that levels of CAR in human epithelial cells play a key role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 47 publications
(82 reference statements)
1
57
0
Order By: Relevance
“…Recently, two studies have described a mechanism by which CAR may regulate epithelial intercellular junctions. CAR was found to control E-cadherin stability at cell-cell contacts by promoting the internalization of E-cadherin [64,65]. CAR phosphorylation by PKCδ was shown to regulate Src-dependent endocytosis of E-cadherin at cell junctions.…”
Section: The Role Of Jam Family Members In Mucosal Epithelial Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two studies have described a mechanism by which CAR may regulate epithelial intercellular junctions. CAR was found to control E-cadherin stability at cell-cell contacts by promoting the internalization of E-cadherin [64,65]. CAR phosphorylation by PKCδ was shown to regulate Src-dependent endocytosis of E-cadherin at cell junctions.…”
Section: The Role Of Jam Family Members In Mucosal Epithelial Barriermentioning
confidence: 99%
“…Specifically, CAR-dependent E-cadherin endocytosis occurred when CAR is not phosphorylated but PKCδ–dependent phosphorylation resulted in the recovery of E-cadherin at adherens junctions (AJs). These data suggest that PKCδ mediated phosphorylation of CAR maintains E-cadherin at junctions and may serve to stabilize epithelial cell-cell adhesion [65]. Furthermore, the above observations suggest that CAR may act preferentially on the maintenance of epithelial AJs instead of TJs.…”
Section: The Role Of Jam Family Members In Mucosal Epithelial Barriermentioning
confidence: 99%
“…The ICD of CAR contains numerous sequences that could be involved in protein-protein interaction and influence endocytosis (32,33). CAR could also regulate the trafficking of other proteins potentially important for CAV-2 entry, as described for E-cadherin (38) or acid sensing ion channel 3 (39). The ICD of CAR could also influence the ECD of CAR.…”
Section: Discussionmentioning
confidence: 99%
“…74,93,94 Similar to JAM-A, CAR can engage in homophilic interactions 95 ; however, it also binds JAML, a JAM-like protein expressed exclusively on PMNs, monocytes, and gd T-cells, 74,96 with high affinity. While these observations marked the CAR-JAML ligand pair as an attractive candidate for PMN trafficking regulation, a recent study found that inhibiting these interactions only had a minor effect on PMN TEM.…”
Section: Tight Junction Signaling and Function During Pmn Transepithementioning
confidence: 99%
“…94 Specifically, PKCd-mediated C-terminal CAR phosphorylation stabilizes E-cadherin at the cell junctions, 94 likely resulting in reduced migratory and proliferative phenotypes.…”
Section: Tight Junction Signaling and Function During Pmn Transepithementioning
confidence: 99%